P‐40: Stereoscopic Cluster Based on Dual‐layer Display. Issue 1 (30th May 2018) - Long, Bin; Yoon, Daekeun; Li, Wenyang; Kusama, Kentaro; Zhang, Zan; Ma, Qing; Han, Rui; Yu, Jie; Chen, Ming
Abstract : In this paper, a 12.3inch cluster using a dual‐layer LCD module is proposed. By using two overlapped LCD panels, we demonstrate the ability to achieve stereoscopic animation and high contrast ratio (>4000:1). Meanwhile, a particular diffusion film was introduced to eliminate the Moiré effect induced by the stacked TFT panels.